FACTORS FORMING DEVIANT BEHAVIOR BETWEEN MINORS - Tajaliyev Abduqodir Abduhakimovich; Imomova Nozimaxon Avazxanovna; Maftunakxon Moydinova (Galaxy International Interdisciplinary Research Journal, 2023)
This article scientifically analyzes the socio-psychological factors influencing the occurrence of deviant behavior among minors and educational measures with children and adolescents with difficult upbringing. In particular, the peculiarities of the social environment, that is, the contradictions between social norms and the individual, and their escalation, are considered in the social characteristics of juveniles.